Legal Regulation On The Implementation Of Electronic Certificates - Irwan Haryowardani (International Journal Of Humanities Education and Social Sciences (IJHESS), 2022)
Land as an economically valuable asset will increase in the future is a strategic option. Based on this, it can be said that land is a very important need for society. To utilize a land or plot of land, a person or community must first have authority over the land or what is known as the right of control over land. With the ownership of the land rights, a person or community can have a basis of authority and obligation and prohibition to do something on the land they own. Based on the background described above, the author is interested in researching the legal arrangements for the implementation of electronic certificates. This study uses theories and possibly hypotheses. This study aims to find a rule of law, legal principles, and legal doctrines to answer legal issues faced. From the results of the study it is known that the provisions of land based on legislation in Indonesia, which is regulated in Law No. 5 of 1960 on basic agrarian principles, which regulates the basics and provisions of the control, ownership, use and utilization of National Agrarian resources in Indonesia, it includes the basics and basic provisions, the rights to the homeland and space as well as land registration. The legal regulation on the implementation of electronic certificates refers to ATR/BPN Ministerial Regulation Number 1 of 2021 concerning electronic certificates. The mechanism for issuing electronic certificates is in accordance with agrarian and Spatial Planning Regulation Number 1 of 2021 concerning electronic certificates in Article 4 paragraph (4) electronic documents issued through electronic systems are authorized using electronic signatures in accordance with statutory provisions and validated by authorized officials or appointed officials and given digital stamps through electronic systems.